2021
DOI: 10.1038/s41556-021-00792-w
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 protects transcription from toxic PARP1 activity during DNA base excision repair

Abstract: Genetic defects in the repair of DNA single-strand breaks (SSBs) can result in neurological disease triggered by toxic activity of the single-strand-break sensor protein PARP1. However, the mechanism(s) by which this toxic PARP1 activity triggers cellular dysfunction are unclear. Here we show that human cells lacking XRCC1 fail to rapidly recover transcription following DNA base damage, a phenotype also observed in patient-derived fibroblasts with XRCC1 mutations and Xrcc1−/− mouse neurons. This defect is caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…Data from the present study combined with the one by the Caldecott lab (Adamowicz et al 2021;Demin et al 2021) are consistent with and extend a model that has previously been proposed by Dianov and Hübscher (Dianov and Hubscher 2013). According to this model, one of the key functions of PARP1 during SSBR comprises the regulation of SSBR capacity and prevention of DSB formation by nuclease attack.…”
Section: Discussionsupporting
confidence: 92%
“…Data from the present study combined with the one by the Caldecott lab (Adamowicz et al 2021;Demin et al 2021) are consistent with and extend a model that has previously been proposed by Dianov and Hübscher (Dianov and Hubscher 2013). According to this model, one of the key functions of PARP1 during SSBR comprises the regulation of SSBR capacity and prevention of DSB formation by nuclease attack.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that the loss of XRCC1 causes PARP1 to exert its intrinsic poisoning activity, leading to the rapid NAD + depletion during treatment with TMZ (Figure 5b). NAD + depletion is seen in various diseases, including the postischemic injury of the heart, brain, liver, and kidney, neurodegeneration, and cancer (Adamowicz et al, 2021; Gujar et al, 2016; Hoch et al, 2017; Pieper et al, 2000). NAD + depletion by its biosynthesis blockade is used to treat cancers and interferes with BER of TMZ‐induced base damage (Goellner et al, 2011; Touat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While the rapid localisation of PARP1 to single-strand breaks has been well characterised, its precise mechanism of localisation to DSBs remains unknown (Liu et al, 2017). In SSB repair, PARP1 and its associated PARylation events recruit X-ray repair crosscomplementing protein 1 (XRCC1) to SSB sites, with XRCC1 functioning as a scaffold for the subsequent binding of SSB repair proteins (Masson et al, 1998;Breslin et al, 2015;Hanzlikova et al, 2017;Adamowicz et al, 2021). It is currently unclear how the cell might differentiate between isolated SSBs and those that occur in very close proximity but on opposite strand (i.e., DSBs) after the initial PARylation.…”
Section: The Role Of Parp In the Immediate-early Double Strand Break Responsementioning
confidence: 99%